Efektivitas Model Learning Cycle 5E dalam Meningkatkan Hasil Belajar Siswa - Salong, Amjad; Lasaiba, Mohammad Amin (SAP (Susunan Artikel Pendidikan), 2024)
Improving educational practices to enhance student learning outcomes has been a central theme in academic research. This study aims at exploring the effectiveness of the 5E Learning Cycle model in improving geography learning outcomes among students. The research method employed was Classroom Action Research conducted at Muhammadiyah Ambon High School from January to May 2022, with a sample of randomly selected 11th-grade classes. The study's findings indicated that the 5E Learning Cycle model effectively enhanced student learning outcomes and engagement. Between Cycle I and Cycle II, learning mastery from cognitive assessments improved. Specifically, there was a 72.5% increase in Cycle I, which improved to 85.0% in Cycle II. Performance assessments showed a 75.0% improvement in Cycle I and an 87.5% in Cycle II. This research demonstrated effectiveness and concluded after Cycle II regarding applying the learning model, the learning process involving teacher and student activities, and student learning outcomes assessed across cognitive, affective, and psychomotor domains.